Teliospore germination and nuclear behaviour in Entyloma mundkuri - GANDHE, R.V. (Indian Phytopathology, 2002)
Teliospore germination in Entyloma mundkuri Patil and Gandhe was studied in detail. During germination, a diploid nucleus undergoes meiosis in the promycelium resulting into four to eight haploid nuclei. Both the divisions take place in the promycelium. Teliospores germinate and develop a cluster of four to eight subcylindrical uninucleate primary sporidia. The compatible primary sporidia fuse ill situ. Primary sporidia develop two types of secondary sporidia. Several aberrations in teliospore germination and nuclear behaviour we e also observed and discussed in this paper.